Auditory habituation to simple tones: reduced evidence for habituation in children compared to adults - Muenssinger, Jana; Stingl, Krunoslav T.; Matuz, Tamara; Binder, Gerhard; Ehehalt, Stefan; Preissl, Hubert (Frontiers in Human Neuroscience, 2013)
Habituation – the response decrement to repetitively presented stimulation - is a basic cognitive capability and suited to investigate development and integrity of the human brain. To evaluate the developmental process of auditory habituation, the current study used magnetoencephalography to investigate auditory habituation, dishabituation and stimulus specificity in children and adults and compared the results between age groups. Twenty-nine children (Mage = 9.69 years, SD ± 0.47) and 14 adults (Mage = 29.29 years, SD ± 3.47) participated in the study and passively listened to a habituation paradigm consisting of 100 trains of tones which were composed of five 500Hz tones, one 750Hz tone (dishabituator) and another two 500Hz tones, respectively while focusing their attention on a silent movie. Adults showed the expected habituation and stimulus specificity within-trains while no response decrement was found between trains. Sensory adaptation or fatigue as a source for response decrement in adults is unlikely due to the strong reaction to the dishabituator (stimulus specificity) and strong mismatch negativity responses. However, in children neither habituation nor dishabituation or stimulus specificity could be found within-trains, response decrement was found across trains. It can be speculated that the differences between children and adults are linked to differences in stimulus processing due to attentional processes. This study shows developmental differences in task-related brain activation and discusses the possible influence of broader concepts such as attention, which should be taken into account when comparing performance in an identical task between age groups.